PENINGKATAN KETERAMPILAN MEMBACA PESERTA DIDIK MENGGUNAKAN MODEL SURVEY, QUESTION, READ, RECITE DAN REVIEW (SQ3R) DI KELAS III SDN 144/VI BANGKO IX - Husni Maulana, Ramzhi; Aryastuti Hasanah, Ika (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Abstrack This research was motivated by the low reading ability of students. The aim of the research is to determine the improvement in reading skills using the SQ3R (Survey, Question, Recite, Read, Review) model in Class III SDN 144/VI Bangko and to measure the achievement of improving reading skills in Indonesian language subjects using the Survey, Question, Recite, Read, Review (SQ3R) model in Class III SDN 144/VI Bangko. This research uses the classroom action research (PTK) method and the research subjects are 23 class III teachers and students. Meanwhile, the research object is through the SQ3R model (survey, question, read, recite, review). Data collection techniques use observation, interviews, documentation techniques. Based on the research results, it shows that the application of the SQ3R model is successful in encouraging students to be more active in the learning process. The teacher applies the SQ3R model by guiding students to observe pictures and predict the content of the story (survey), formulate questions (question), read the text in groups (read), retell the content of the story (recite), and review the content of the reading through class discussion (review). This increase can be seen from the results of the student observation sheet where in Cycle I, meeting I reached 53.26 and meeting II 64.56, with an average of 58.91. In Cycle II, meeting I increased to 77.60 and meeting II to 88.69, with an average of 83.15 which is considered good. It can be concluded that the SQ3R model research can be an effective strategy in improving students' reading skills, so that it can be applied in Indonesian language learning. Keywords: Improvement, Reading Skills, Survey Model, Question, Read, Recite, and Review (SQ3R)